2022
DOI: 10.3389/fmed.2022.856156
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Toward the Prevention of COVID-19 in Bangladesh: A Systematic Review and Meta-Analysis

Abstract: BackgroundNumerous studies on knowledge, attitude, and practice (KAP) about the prevention of COVID-19 infections are available in Bangladeshi contexts, with results that vary significantly. However, no earlier attempt has been made to analyze the available COVID-19 KAP studies in Bangladesh, which is incorporated in this meta-analysis for the first time.MethodsFollowing the PRISMA guidelines, articles relevant to COVID-19 KAP that were conducted among the Bangladeshi population were found in databases such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…These studies in different countries revealed that the results differed among nations and were impacted by the types of human settlements. As a result, while creating health programs for COVID-19 and any future epidemics or pandemics, health and education agencies in various nations should strengthen their preventative measures by building specialized measures aimed at individuals in different settlements [76][77][78][79][80][81][82][83]. Knowledge disparity has been extensively studied in health communication.…”
Section: Discussionmentioning
confidence: 99%
“…These studies in different countries revealed that the results differed among nations and were impacted by the types of human settlements. As a result, while creating health programs for COVID-19 and any future epidemics or pandemics, health and education agencies in various nations should strengthen their preventative measures by building specialized measures aimed at individuals in different settlements [76][77][78][79][80][81][82][83]. Knowledge disparity has been extensively studied in health communication.…”
Section: Discussionmentioning
confidence: 99%
“…Although overall COVID-19 preventative practice was good, subgroup analysis found that men had a poor practice toward controlling the infection. The practice of avoiding crowded places (70.15%) and maintaining social distance (77.17%) was found to be satisfactory in institution-based studies [11].…”
Section: Discussionmentioning
confidence: 95%
“…1 Increased understanding of the epidemiology of the pandemic led to the application of several strategies including both pharmacological and non-pharmacological methods to cut down the widespread of COVID-19 virus transmission in the world. 2 4 Many countries subsequently imposed national lockdowns by closing all schools and workplaces, which led to increased virtual learning globally. Social distancing measures were enforced and movement restrictions were implemented by preventing people from visiting public places or organizing public meetings that will allow the physical meeting of people from different households all aimed at reducing the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%